2010
DOI: 10.1177/112067211002000508
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Not Performing LASIK in Refractive Surgery Candidates in Yemen

Abstract: Patients who request refractive surgery have a variety of problems and attention must be given to these patients. Suboptimal corneal thickness, high amount of refractive error, and keratoconus were found to be the leading causes of not performing LASIK in Yemeni patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
3
10
0
Order By: Relevance
“…Studies would suggest that between 25 to 34 per cent of patients requesting a consultation may not be appropriate for LASIK surgery. [18][19][20] This number is consistent with our experience.…”
Section: Patient Selectionsupporting
confidence: 92%
“…Studies would suggest that between 25 to 34 per cent of patients requesting a consultation may not be appropriate for LASIK surgery. [18][19][20] This number is consistent with our experience.…”
Section: Patient Selectionsupporting
confidence: 92%
“…37 In Yemen, prevalences of 15.5% of keratoconus and 9.4% of forme fruste keratoconus were found among refractive surgery candidates. 33 In a study in the United States, 25.5% of eyes evaluated for refractive surgery met the Rabinowitz criteria for keratoconus suspect. 34 A vast majority of the studies state that the age of onset of the disease is between 20 and 30 years.…”
Section: Epidemiologymentioning
confidence: 99%
“…30,31 The disease has been shown to be more prevalent also in patients searching for refractive surgery, as a consequence of self-selection bias, due to their refractive error. [33][34][35][36][37] A study in Colombia reported 3.9% prevalence in a group of patients that underwent an ophthalmic evaluation in a refractive surgery center. 37 In Yemen, prevalences of 15.5% of keratoconus and 9.4% of forme fruste keratoconus were found among refractive surgery candidates.…”
Section: Epidemiologymentioning
confidence: 99%
“…[1] The most common reasons for rejection are suboptimal corneal thickness, high myopia, keratoconus and forme fruste keratoconus (keratoconus suspect). Alternatives to LASIK for the correction of moderate to high myopia include clear lens extraction (CLE) and implantation of a phakic intraocular lens (PIOL).…”
Section: Introductionmentioning
confidence: 99%